The Islamic Glorious Epoch through the March of History (Khairulummah, 2023)
This study discusses the key elements that developed Islam's "Golden Age" and their contributions. Beginning with the reign of Abbasid Caliph Harun al-Rashid (c. 786–809) and concluding with the Abbasid Caliphate's fall with the Mongol invasions and the sack of Baghdad in 1258 CE, this period of Islamic growth lasted nearly five centuries.  On the other hand, some scholars define Islam's Golden Age more broadly and across a longer period of time.  All concur, however, that the Golden Age represents a truly remarkable period in human history that spans several centuries and includes the exceptional accomplishments of Islamic scholars, humanists, and scientists across a wide range of disciplines, including finance, mathematics, astronomy, medicine, and Islamic and European monetary systems.  The main contributions to human progress made by the Abbasid, Fatimid, and Umayyad dynasties in Baghdad, Cairo, and Andalusia are briefly listed here. It also provides several examples of the lasting contributions made by the Islamic Golden Age from antiquity to the present, many of which laid the foundation for a prosperous future for both Islamic societies and the world at large.